Implications of the Application of Flipped Classroom Learning Media to Self-efficacy and Student Learning Participant - Hesty Prima Rini; Wilma Cordelia Izaak (Journal of Economics, Business, and Government Challenges, 2018)
The importance of learning activeness of UPN Veteran Jawa Timur management program students in the success of the learning process, one of which is influenced by internal factors inherent in students (talents, interests, and IQ), one of which is shown by the level of self-efficacy. This study aims to analyze the implications of application of flipped class room learning media to increase self-efficacy and student learning activities. This research uses quasi experiment or pseudo experiment with one-group-pretest-posttest design model, where the research will be conducted in two cycles of assessment that is the first cycle in the period before the learning process "Interactive Classroom Activities" and "Explicit Instruction Methods" after seven initial meetings before Midtest and after Midtest. This research process is done cyclically as suggested by Kemmis & McTaggart (1988) with respect to plan, implementation, monitoring, and reflection. Test reliability is done by technique test-retest (repeat measurement). The population in this study are all students of Management Faculty of Economics and Business UPN Veteran Jawa Timur. The sample in this research is student of UPN Veteran Jawa Timur Management class of 2015-2016 as experiment class with number of 30 people. Based on the classroom action research conducted by the influence of self-efficacy on student activity, the effect of using flipped classroom learning media on self-efficacy in two different cycles proved to have positive but not significant effect. Second, the influence of the use of flipped classroom learning media visually proved to have a positive and significant impact on student activeness.